2020
DOI: 10.3390/ani10040600
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Agroindustrial Byproducts to Light Lambs: Influence on Growth Performance, Diet Digestibility, Nitrogen Balance, Ruminal Fermentation, and Plasma Metabolites

Abstract: The objective of this study was to evaluate the effect of replacing cereals and protein concentrates in a high-cereal concentrate (control) for light lambs with corn distiller’s dried grains with solubles (DDGS; 18%), dried citrus pulp (DCP; 18%), and exhausted olive cake (EOC; 8%) in a byproduct (BYP) concentrate on growth performance, digestibility, ruminal fermentation, and plasma metabolites. Two homogeneous groups of Lacaune lambs (13.8 kg ± 0.25 kg) were fed one of each concentrates and barley straw ad l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
(48 reference statements)
1
25
1
Order By: Relevance
“…The present study analyzes the quality of meat from lambs fed either a high-cereal concentrate or a concentrate containing corn DDGS, DCP, and EOC. Previously, de Evan et al [4] showed that there were no differences between concentrates in growing performance, digestibility of nutrients, and animal health of the lambs. There were also no differences in hot and cold carcass weights, which reached 14.4 and 13.6 kg for the CON and 14.2 and 13.6 kg for the BYP groups, respectively [4].…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The present study analyzes the quality of meat from lambs fed either a high-cereal concentrate or a concentrate containing corn DDGS, DCP, and EOC. Previously, de Evan et al [4] showed that there were no differences between concentrates in growing performance, digestibility of nutrients, and animal health of the lambs. There were also no differences in hot and cold carcass weights, which reached 14.4 and 13.6 kg for the CON and 14.2 and 13.6 kg for the BYP groups, respectively [4].…”
Section: Resultsmentioning
confidence: 97%
“…This is a companion paper to the study of de Evan et al [4], who reported the effects of by-product (BYP) concentrate on growth performance, diet digestibility, blood parameters, and ruminal fermentation of the lambs. The animals used in this experiment were cared for and handled in accordance with the Spanish guidelines for experimental animal protection.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations